2021
DOI: 10.1016/j.ajpc.2021.100219
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in cardio-metabolic risk factors and atherosclerotic cardiovascular disease among Asian groups in the United States

Abstract: Objective The Asian American population in the U.S. comprises various, ethnically diverse subgroups. Traditionally, this population has been studied as a single, aggregated group, potentially masking differences in risk among subgroups. Analyses using disaggregated data can help better characterize the health needs of different Asian subpopulations and inform targeted, effective public health interventions. We assessed the prevalence of cardiovascular disease (CVD) risk factors and atherosclerotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…At present due to sample size limitations ethnicity is captured in three categories, yet this is likely to be an oversimplification. For example, there are clear differences in cardiometabolic risk among different Asian ethnic groups, 53 and between Black Africans and Black Caribbeans. 54 PsyMetRiC cannot at present capture those differences.…”
Section: Discussionmentioning
confidence: 99%
“…At present due to sample size limitations ethnicity is captured in three categories, yet this is likely to be an oversimplification. For example, there are clear differences in cardiometabolic risk among different Asian ethnic groups, 53 and between Black Africans and Black Caribbeans. 54 PsyMetRiC cannot at present capture those differences.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown heterogeneity in cardiovascular risk factor profile among Asian subgroups with a trend towards higher prevalence of diabetes mellitus in Asian Indians, higher prevalence of hypertension among Filipinos, and generally low risk factor burden among Chinese. ( Satish et al, 2021 , Koirala et al, 2021 , Dong, 2021 ) These differences can likely be attributed to varying degrees of acculturation as a result of cultural practices, history, language, time prior to moving to the U.S. and biological factors that are unique to each ethnic group. ( Needham et al, 2017 , Lieber et al, 2001 , Vargas and Jurado, 2015 ) Indeed Asian ethnic groups have different predilections to acculturation (embracing host cultural norms including values, attitudes and beliefs) versus enculturation (resocialization to ethnic cultural norms) though using U.S. birth and duration of time spent in the U.S. as proxies may not fully capture the dimensions of these constructs.…”
Section: Discussionmentioning
confidence: 99%
“…( Gupta et al, 2002 , Zaman et al, 2001 , Mendis and Ekanayake, 1994 ) This inherent high risk may be exacerbated during the process of acculturation among Asian immigrants. ( Al-Sofiani et al, 2020 ) With the increasing number of individuals of Asian descent in the U.S. and heterogenous cardiovascular disease risk factor profiles among Asian Americans, ( Satish et al, 2021 , Rodriguez et al, 2019 ) there is a need to examine health disparities among various Asian subgroups using a racial and cultural framework ( Wong et al, 2019 ) that examines Asian American health within the context of cultural integration. This analysis may identify high-risk Asian American subgroups ( Palaniappan et al, 2010 ) and shed light on how acculturation in Asian individuals may be associated with cardiovascular risk factors and ASCVD.…”
Section: Introductionmentioning
confidence: 99%
“…To ascertain differences among NH Asians subgroups, multivariable-adjusted logistic regression models as above were used to study the association of Asian ethnic groups and sufficient physical activity (Chinese as reference given that they have a lower cardiovascular risk factor profile compared with other Asian groups 10 ).…”
Section: Methodsmentioning
confidence: 99%